Gender Wage Gap and the Welfare-Enhancing Role of Parental Leave Rules - Spencer Bastani; Tomer Blumkin; Luca Micheletto (ifo DICE Report, 2017)
A large body of empirical evidence documents the gender variation in labour market outcomes. A major factor that contributes to persistent gender gaps in labour market performance is women's traditional role in the household. Child-related absences from work imply that women accumulate less job experience, are more prone to career discontinuities and, hence, suffer a motherhood penalty. We highlight how the fundamental gender-driven career/family conflict faced by workers in the labour market may create a normative justification for parental leave rules as a means to enhance efficiency and alleviate the gender pay gap.
Keywords: J13; J16; J31; 330; Lohnstruktur; Geschlechterunterschiede; Geschlechterdiskriminierung; Geschlechterrolle; Fraueneinkommen; Elternzeit